Training In Writing Abstracts of Scientific Works at Jam’iyah Mahmudiyah Islamic High School (STAI-JM), Tanjung Pura, Langkat District - Deliana; Nurlela; Rangkuti, Rahmadsyah (Talenta Publisher, 2023)
Jam'iyah Mahmudiyah Islamic College (STAI-JM) is located in Tanjung Pura, Langkat district, which has five fields of study. At this high school there has never been any training in writing scientific works, either from within the high school itself or from outside the school. One form of writing scientific works is writing abstracts. An abstract is a short summary of scientific work (such as a thesis, dissertation, or research article). The abstract is a very important part of writing scientific works. The abstract form can be packaged nicely and attractively, so that readers can understand the entire contents of the research. The aim of the community service team (PKM) program activities is to practice writing abstracts of scientific work so that students are able to create abstracts from the results of their research briefly, clearly and measurably. The approach used is to collaborate with partners, the Government and STAI-JM teaching staff with training activities and mentoring methods for writing abstracts of scientific papers. This training was considered successful in increasing partners' knowledge and skills in writing abstracts.